Hubungan tekanan akuntabilitas, audit judgement performance, dan effort - Muhsin Muhsin (Jurnal Akuntansi dan Auditing Indonesia, 2016)
The aim of this study is to examine the relationship between accountability pressure, audit judgment performance, and effort in the Audit Board of the Republic of Indonesia central (BPK RI Central). The samples of the study were auditors that work in the Audit Board of the Republic of Indonesia central office in Jakarta. There were 285 questionnaires that were handed out, but only 198 questionnaires were handed in. There were only 90 data that can be analyzed. The data were analyzed using analysis technic of SEM program Warp PLS 4.0. The result of the study shows that the accountability pressure has positive and significant influence toward effort; effort has positive and significant influence toward audit judgment performance; and accountability pressure has positive and significant influence toward audit judgment performance.